Prevalencia y factores de riesgo asociados a tuberculosis pulmonar en pacientes atendidos en el Hospital San Vicente de Paúl de Pasaje. - Pullaguari Montaño, Andrea Michelle (2017)
The Pulmonary tuberculosis is a disease that affects the life quality of the patient that was diagnosed, the treatment requires changes in lifestyle, as this depends on the effectiveness of treatment. This investigation had like an objective to determine the prevalence and risk factors associated in patients with pulmonary tuberculosis, for which was identified cases by risk factors, age, sex and laboratory. The research was descriptive cross with a universe of 43 patients in the period from January to December of 2015. Data were obtained by reviewing the medical histories, analyzed in the Excel statistical package. The results showed that 69.77% was diagnosed with Baciloscopia positive. Risk factors associated firstly were the carriers of the Human Immunodeficiency Virus with 34.88%, followed by alcohol, snuff or some kind of drug with a 29.93%; The age range with greater predisposition to developing the disease was 15 to 30 years representing 48.84%. A higher percentage of men prevalence was observed in 62.79%. Pulmonary tuberculosis is the main cause in patients with human immunodeficiency virus most prevalent in men. Keywords: pulmonary tuberculosis; Prevalence, age, risk factors, gender.